Expanding the Traditional History and Physical Examination to Address Chronic Diseases and Social Needs: A Multisite Randomized Control Trial of 4 Medical Schools. (November 2020) - Kirley, Kate; Hayer, Rupinder; Khan, Tamkeen; Johnson, Eric; Sanchez, Erin Stephany; Kosowicz, Lynn; Terry, Valerie; Henderson, David; Krebsbach, Cory; Park, Yoon Soo; Dekhtyar, Michael; Williams, Brent C.
Abstract : Purpose: This study gathers validity evidence of an expanded History and Physical examination (H&P 360) to address chronic diseases through incorporation of biopsychosocial elements that are lacking in traditional H&P assessments via a multisite randomized controlled trial among medical students. Method: Third- and fourth-year medical students (n = 159) at 4 schools participated in an Objective Structured Clinical Examination designed with 2 cases for chronic disease. Students were randomized into the treatment group, which involved brief written instructions on how to use the H&P 360 followed by a standardized patient (SP) interaction, or the control group, which used the traditional H&P in an SP interaction without additional instructions. Validity evidence was gathered for content (alignment with an empirically derived expanded history list), response process (feedback from raters and learners on the process), internal structure (reliability and item-level psychometrics), relations to other variables (comparison between treatment and control groups), and consequences (survey results from learners on experience). Results: H&P 360 items were blueprinted by faculty experts. SP observation checklist grading was consistent, and postassessment debrief confirmed favorable educational experience among learners. The reliability of the H&P 360 was .76. Overall mean scores on the H&P 360 content (mean = 15.96, standard deviation [SD] = 3.66) were significantly higher compared with the traditional H&P (mean = 10.99, SD = 2.69, Cohen's d = 1.17, P < .001). Conclusions: Medical students using the H&P 360 collected significantly more biopsychosocial information compared with students using the traditional H&P, providing empirical support for teaching and assessing biopsychosocial information. The assessment demonstrated strong validity evidence supporting the use of the H&P 360 assessment in medical schools. Abstract : Supplemental Digital Content is available in the text.